2015
DOI: 10.11646/zootaxa.3919.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Alitta succinea (Leuckart, 1847) and reinstatement of A. acutifolia (Ehlers, 1901) n. comb. based upon morphological and molecular data (Polychaeta: Nereididae)

Abstract: The nereidid worm Alitta succinea (Leuckart, 1847), described from Western Germany, has been considered by some authors as a widespread and alien invasive species, or else as a group of morphologically indistinguishable species. Neither idea has yet been supported by critical taxonomic revisions of relevant material. Most characterizations of A. succinea were based upon a mixture of morphological features from specimens from the type locality and from other regions. Moreover, four species described from Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
1
32
0
2
Order By: Relevance
“…The anterior-most rows have P-bars alternating with conical or pyramidal paragnaths in a similar way as in Pseudonereis (Fig. 6D–F), which has been also reported for Alitta (Villalobos-Guerrero and Carrera-Parra 2015). Therefore, P-bars are not an exclusive feature of Pseudonereis as Bakken et al (2009) concluded.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The anterior-most rows have P-bars alternating with conical or pyramidal paragnaths in a similar way as in Pseudonereis (Fig. 6D–F), which has been also reported for Alitta (Villalobos-Guerrero and Carrera-Parra 2015). Therefore, P-bars are not an exclusive feature of Pseudonereis as Bakken et al (2009) concluded.…”
Section: Resultssupporting
confidence: 83%
“…6H); these modified structures were regarded as melted paragnaths (Bakken et al 2009). However, Glasby et al (2011) suggested limiting use of the term for conical paragnaths mounted on a plate-like basement as occurs in Neanthes pachychaeta (Fauvel, 1918), and Villalobos-Guerrero and Carrera-Parra (2015) found paragnaths on a soft basement in Alitta acutifolia (Ehlers, 1901). Because neither a basement is present in Nereis confusa sp.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the male individuals described by Villalobos-Guerrero (2012) and Villalobos-Guerrero & Carrera-Parra (2015) were in earlier stages of epitoky or, perhaps, A. succinea comprises a species complex. There are no reports of the presence of serrated papillae in the ventral cirri in other studies of Alitta species, or other genera of the family.…”
Section: Reproductionmentioning
confidence: 98%
“…This species can be found in a variety of marine and estuarine intertidal to subtidal substrates, including infaunal and epifaunal locations, sand and mud bottoms, seagrass meadows, and rocky benthic areas (Pardo & Dauer 2003;Gillet et al 2011). The species is semelparous, and individuals die soon after a single reproductive event (Villalobos-Guerrero 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation